2015
DOI: 10.4238/2015.december.28.19
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-146a induces vascular smooth muscle cell apoptosis in a rat model of coronary heart disease via NF-κB pathway

Abstract: ABSTRACT. The aim of this study was to investigate the role of miRNA146a in modulating the function of vascular smooth muscle cells in a rat model of coronary heart disease. Vascular smooth muscle cells were isolated and cultured from the rat coronary heart disease model and normal rats (controls). miRNA-146a levels were measured in vascular smooth muscle cells obtained from rats with coronary heart disease and control rats. The proliferation, growth, apoptosis, and activation of the NF-κB pathway in the vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
0
25
0
2
Order By: Relevance
“…The results of the present study indicate that the therapeutic effects of ESCs improve the atherosclerosis indices in a rat model of CAD compared with control rats. Wu et al (24) reported that miRNA-146a induced vascular smooth muscle cell apoptosis via the NF-κB signaling pathway. In the present study, ESCs therapy decreased miRNA-146a expression and increased VEGF expression in the myocardium of rats with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study indicate that the therapeutic effects of ESCs improve the atherosclerosis indices in a rat model of CAD compared with control rats. Wu et al (24) reported that miRNA-146a induced vascular smooth muscle cell apoptosis via the NF-κB signaling pathway. In the present study, ESCs therapy decreased miRNA-146a expression and increased VEGF expression in the myocardium of rats with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-92a overexpression inhibits H 2 O 2 -induced VSMCs apoptosis and senescence by suppressing both mitogen-activated protein kinase 4 (MKK4) and JNK1 pathways [81]. Another miRNA, miRNA-146a was found to induce VSMC apoptosis via activation of the NF- κ B signaling pathway [82]. …”
Section: Mirnas and Vascular Agingmentioning
confidence: 99%
“…It is necessary to identify disease-specific miRNAs and their targets to understand their roles in disease (29)(30)(31). It has been reported that various miRNAs participate in mediating the functions of VSMCs, including miR-21, miR-214 and miR-146a (32)(33)(34). In the present study, the expression level of miR-24-3p in the blood samples of 30 patients with CHD was explored using RT-qPCR and it was found that the miRNA-24-3p level was higher in the blood samples of patients with CHD compared with the normal controls.…”
Section: Discussionmentioning
confidence: 99%